Higher Wages, Less Gym Time? The Effects of Minimum Wages on Time Use. (1st April 2019) - Lenhart, Otto
Abstract : This study examines the effects of minimum wages on time use. Analyzing data from the American Time Use Survey from 2003 to 2017, I investigate the role of time allocated toward exercise and other health‐enhancing activities as a potential mechanism underlying the link between minimum wages and health. The study finds that a 1 increase in minimum wages is associated with reductions in exercising and total personal health time by 13 and 20 minutes during the week, respectively. This decline in health time is fully reallocated toward additional leisure time. The results are largely driven by males and employed individuals.